Carlos Fernández Shaw, Poesías completas. Pról. de Melchor Fernández Almagro. Gredos, Madrid, 1966; 617 pp. - Vergara, M. A. (El Colegio de México, 2007)
Se reseñó el libro: Poesías completas. Pról. de Melchor Fernández